2010
DOI: 10.1103/physreva.82.032324
|View full text |Cite
|
Sign up to set email alerts
|

Quantum decoherence in noninertial frames

Abstract: Quantum decoherence, which appears when a system interacts with its environment in an irreversible way, plays a fundamental role in the description of quantum-to-classical transitions and has been successfully applied in some important experiments. Here, we study the decoherence in noninertial frames for the first time. It is shown that the decoherence and loss of the entanglement generated by the Unruh effect will influence each other remarkably. It is interesting to note that in the case of the total system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 30 publications
0
58
1
Order By: Relevance
“…Actually, Unruh effect is like decoherent effect, which can be viewed as quantum noise channel, as interpreted in the article [22]. Some researchers studied the influence of noninertial frame to quantum correlations [23][24][25][26][27]. They showed that the Unruh effect degrades the quantum correlations in different modes of various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, Unruh effect is like decoherent effect, which can be viewed as quantum noise channel, as interpreted in the article [22]. Some researchers studied the influence of noninertial frame to quantum correlations [23][24][25][26][27]. They showed that the Unruh effect degrades the quantum correlations in different modes of various fields.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus independent of the way the reduced state is computed, wether by using fermion-qubit mappings as it was done in previous works [2][3][4][5][6][7][8][9][10][11][12]16], or by any other means.…”
Section: The Main Resultsmentioning
confidence: 99%
“…al [3]. In [4], the effect of quantum decoherence generated by the Unruh effect on the dynamics of a maximum entangled state is discussed. Said and Adami [5] have invistigated the Einstein-Podolsky-Rosen correlation in Kerr-Newman space time.…”
Section: Introductionmentioning
confidence: 99%